Avoiding OHSS: controlled ovarian low-dose stimulation in women with PCOS = Vermeidung eines OHSS : kontrollierte ovarielle Low-Dose-Stimulation für IVF und ICSI bei Frauen mit polyzystischem Ovarsyndrom - Fischer, D.; Rösner, Sabine (Geburtshilfe und Frauenheilkunde, 2015)
The polycystic ovary syndrome is a common endocrine disorder which influences outcome and potential risks involved with controlled ovarian stimulation for artificial reproductive techniques (ART). Concrete practical recommendations for the dosage of gonadotropins, the preferred protocol and preventive methods to avoid ovarian hyperstimulation syndrome (OHSS) are lacking. We present retrospective data of 235 individually calculated gonadotropin low-dose stimulations for ART in a single center from 2012 to 2014. Clinical data and outcome parameter of patients diagnosed with PCOS according to Rotterdam criteria (n = 39) were compared with patients without PCOS (n = 196). The starting dose of gonadotropins was individually calculated depending on patientsʼ age, BMI, ovarian reserve, ovarian response in previous cycles, and diagnostic criteria of PCOS. Mean age and duration of infertility did not differ between the groups, whereas mean BMI (p = 0.007) and AMH (p < 0.001) were higher in the PCOS-group. A lower mean FSH-starting and maximum dose was administered to women with PCOS (p < 0.001). The biochemical pregnancy rate of 42.4% and the clinical pregnancy rate of 32.2% for PCOS-patients did not differ from those of the control group (42.2% and 34.4% respectively). Neither mild, nor moderate or severe manifestation of OHSS occurred significantly more often in patients with PCOS. Our study supports the use of a calculated low-dose FSH-stimulation strategy in ART for patients with PCOS. Further randomized clinical trials should confirm this strategy and lead to define individual risk factors for OHSS, which can be used for recommendation of safer ART-techniques like in vitro maturation.
Gesehen am 05.02.2019